Pengaruh Celebrity Endorser terhadap Purchase Intention: Peran Mediasi Brand Credibility dan Brand Attitude pada Produk Make Over Cosmetics - Damayanti, Dea; Wahyudi, Handri Dian (Jurnal Nusantara Aplikasi Manajemen Bisnis, 2022)
This study aims to test whether the effectiveness of celebrity endorsers, brand credibility, brand attitude is a factor in purchase intention, brand credibility is a mediation for brand attitude and brand credibility and brand attitude is a mediation. A total of 314 who knew Make Over Cosmetics and celebrity endorser Tasya Farasya were sampled to be tested by distributing online questionnaires with hypothesis testing using WarpPLS. The result, celebrity endorser has a significant impact on purchase intention, celebrity endorser has a significant impact on brand credibility, brand credibility has a significant impact on brand attitude, brand credibility has a significant impact on purchase intention, brand attitude has a significant impact on purchase intention and brand credibility and brand attitude have succeeded in becoming mediating variable.